2013
DOI: 10.3390/ijerph10052058
|View full text |Cite
|
Sign up to set email alerts
|

A Higher Prevalence Rate of Campylobacter in Retail Beef Livers Compared to Other Beef and Pork Meat Cuts

Abstract: The objectives of this study were to determine the prevalence of Campylobacter jejuni and Campylobacter coli in retail beef, beef livers, and pork meats purchased from the Tulsa (OK, USA) area and to further characterize the isolates obtained through antimicrobial susceptibility testing. A total of 97 chilled retail beef (50 beef livers and 47 other cuts), and 100 pork samples were collected. The prevalence of Campylobacter in beef livers was 39/50 (78%), while no Campylobacter was isolated from the other beef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
66
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 41 publications
13
66
1
Order By: Relevance
“…33,38,41 Furthermore, the prevalence of C. coli in this study is similar to that reported in other countries. 21,62,69,92 The distribution of C. jejuni and C. coli can be influenced by many factors, including seasonality, age of the animal, and geographical locations. For example, Sanad et al 75 reported a higher prevalence of C. coli in cattle fecal samples collected from the Southern United States in comparison to those from Northern, Midwestern, and Eastern regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,38,41 Furthermore, the prevalence of C. coli in this study is similar to that reported in other countries. 21,62,69,92 The distribution of C. jejuni and C. coli can be influenced by many factors, including seasonality, age of the animal, and geographical locations. For example, Sanad et al 75 reported a higher prevalence of C. coli in cattle fecal samples collected from the Southern United States in comparison to those from Northern, Midwestern, and Eastern regions.…”
Section: Discussionmentioning
confidence: 99%
“…The results are comparable to those reported by other investigators. 12,62,64,68,92 Macrolides (erythromycin and tylosin) resistance was primarily associated with most (91.7%) of the MDR isolates. A similar association has been reported in previous studies, although no genetic basis has been described.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 552 Campylobacter isolates (281 Campylobacter jejuni and 271 Campylobacter coli ) previously isolated from retail meat samples in our laboratory [21,22] were used for arsenic resistance profiling in this study. The isolates were from chicken ( n = 130), turkey ( n = 19), pork ( n = 6), beef livers ( n = 102), chicken livers ( n = 272), and chicken gizzards ( n = 23).…”
Section: Methodsmentioning
confidence: 99%
“…Cultural and dietary differences could influence the relative contribution of sources of foodborne disease in France and the United Kingdom. For example, chicken consumption is higher in the United Kingdom (30 kg/person/year) compared to France (25 kg/person/year) (50), where other known infection sources, including ruminant offal and veal (51)(52)(53)(54), form a greater proportion of the diet. Factors associated with food preparation may also be significant, but analysis of a larger data set of French clinical isolates would be necessary to achieve a more representative description of human C. jejuni contamination routes in France.…”
Section: Fig 4 Assignment To Source Of British and French Human Clinimentioning
confidence: 99%